An approximation to the use of the subjunctive mood in the Sociolinguistic Corpus of Mexico City - Lastra, Yolanda; Martín Butragueño, Pedro (Boletín de Filología, 2012)
The main goal of this paper is to study the vitality of the subjunctive in theSpanish speech of Mexico City and find alternations with the indicative. To this purpose 1164 samples of subjunctive forms in 18 speakers from the Sociolinguistic Corpus of Mexico City were examined. As linguistic variables, tense, the conventionality of the construction, the form of the utterance, its syntactic context, and main semantic-pragmatic values were analyzed; polarity, factuality, probability, assertiveness and interchangeability with the indicative were also taken into account. The sociolinguistic variables considered were level of education, age, and gender. The study reaffirms the full vitality of the subjunctive (especially in people with more education, youth and women). The most common subjunctive tenses are the present and the past. Syntactic contexts and semantic and pragmatic values are important to characterize the use of the subjunctive, but in order to understand the alternation with the indicative, it is necessary to consider the factuality, probability and assertiveness involved in each specific instance. More detailed study of the 439 cases of relative interchangeability with the indicative could be carried out.